Nomogram for Predicting Anastomotic Leakage after Rectal Cancer Surgery in Elderly Patients with Dysfunctional Stomata - Li, Chuangkun (Cancer Manag Res, 2021)
PURPOSE: Anastomotic leakage after rectal cancer surgery in elderly patients is a critical challenge. Many risk factors have been found and many interventions tried, but anastomotic leakage in elderly patients remains difficult to deal with. This study aimed to create a nomogram for predicting anastomotic leakage after rectal surgery in elderly rectal cancer patients with dysfunctional stomata. METHODS: We collected data from 326 consecutive elderly patients with dysfunctional stomata after rectal cancer surgery at the Sixth Affiliated Hospital, Sun Yat-Sen University from January 2014 to December 2019. Risk factors of anastomotic leakage were identified with multivariate logistic regression and used to create a nomogram. Predictive performance was evaluated by the area under the receiver-operating characteristic (ROC) curve. RESULTS: American Society of Anesthesiologists score ≥3, male sex, and neoadjuvant radiotherapy were identified as significantly associated factors that could be combined for accurate prediction of anastomotic leakage on multivariate logistic regression and development of a nomogram.The area under the ROC curve for this model was 0.645. The C-index value for this model was 0.645, indicating moderate predictive ability of the risk of anastomotic leakage. CONCLUSION: The nomogram showed good ability to predict anastomotic leakage in elderly patients with rectal cancer after surgery, and might be helpful in providing a reference point for selection of surgical procedures and perioperative treatment.